Impact of a booster dose on SARS-CoV2 mRNA vaccine-specific humoral-, B- and T cell immunity in pediatric stem cell transplant recipients - Thole, Linda Marie Laura; Tóth, Laura; Proß, Vanessa; Siegle, Janine; Stahl, Carolin; Hermsdorf, Georg; Knabe, Annette; Winkler, Annika; Schrezenmeier, Eva; Ludwig, Carolin; Eckert, Cornelia; Eggert, Angelika; et al. (Frontiers in Immunology, 2023)
Stem cell transplant recipients (SCTR) are imperiled to increased risks after SARS-CoV2 infection, supporting the need for effective vaccination strategies for this vulnerable group. With respect to pediatric patients, data on immunogenicity of SARS-CoV2 mRNA-based vaccination is limited. We therefore comprehensively examined specific humoral, B- and T cell responses in a cohort of 2-19 year old SCTR after the second and third vaccine dose. Only after booster vaccination, transplant recipients reached similar levels of vaccine-specific IgG, IgA and neutralizing antibodies against omicron variant as age-matched controls. Although frequencies of SARS-CoV2 specific B cells increased after the third dose, they were still fourfold reduced in patients compared to controls. Overall, the majority of individuals enrolled mounted SARS-CoV2 Spike protein-specific CD4+ T helper cell responses with patients showing significantly higher portions than controls after the third dose. With respect to functionality, however, SCTR were characterized by reduced frequencies of specific interferon gamma producing CD4+ T cells, along with an increase in IL-2 producers. In summary, our data identify distinct quantitative and qualitative impairments within the SARS-CoV2 vaccination specific B- and CD4+ T cell compartments. More importantly, humoral analyses highlight the need for a booster vaccination of SCTR particularly for development of neutralizing antibodies.